1987
DOI: 10.1067/mva.1987.avs0050342
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte depletion enhances cultured endothelial retention on vascular prostheses

Abstract: Approximately 90% of endothelial cells that are seeded or cultured onto vascular prostheses are lost from the flow surface within 24 hours of implantation. To determine the contribution of leukocytes to endothelial cell loss, 111In-labeled, cultured canine jugular venous endothelial cells were grown to confluence on fibronectin-coated polyester elastomer tubes measuring 4 mm inner diameter and 30 mm in length. Autogenous cell-lined tubes were implanted as bilateral carotid replacement grafts in six dogs made l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1,2 We can hypothesize that the latter is caused by both expression of leukocyte adhesion molecules and production of cytokines by ECs activated by the underlying polymer surface.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 We can hypothesize that the latter is caused by both expression of leukocyte adhesion molecules and production of cytokines by ECs activated by the underlying polymer surface.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas control grafts exhibited occasional white cells, the density of white cells on bare areas of sodded graft surfaces was significantly different. Herring et al 19 and Emerick et al 20 indicate that significant activation and attraction of leukocytes occur after implantation of endothelialized prosthetic grafts. We therefore suggest that a major factor in the early healing of endothelial cell transplanted grafts may be the sequestration of leukocytes to areas of graft that have not been completely endothelialized.…”
Section: Discussionmentioning
confidence: 99%
“…Since our own investigations have also shown no significant effect on endothelial leukocyte adhesion molecule expression during EC culture on an artificial surface, it is our belief that the activated ECs found in implanted grafts (Emerick & Herring, 1989) are stimulated by the presence of an 'external' endothelial activator in the blood or the surrounding tissue after implantation of the endothelialized artificial graft. Judged by the finding that ECs attached to an artificial surface can still respond to an activating stimulus, this activator could very well be a cytokine.…”
Section: Endothelial Activationmentioning
confidence: 98%
“…In vivo experiments have shown that loss of seeded endothelial cells is not simply due to shear forces associated with blood flow, but also indicate that massive leukocyte (white blood cell) infiltration is involved in endothelial cell detachment (Emerick et al, 1989).…”
Section: Endothelialization Of Small-diameter Vascular Prosthesesmentioning
confidence: 99%